If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(h + -1) = 90 Reorder the terms: 10(-1 + h) = 90 (-1 * 10 + h * 10) = 90 (-10 + 10h) = 90 Solving -10 + 10h = 90 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 10h = 90 + 10 Combine like terms: -10 + 10 = 0 0 + 10h = 90 + 10 10h = 90 + 10 Combine like terms: 90 + 10 = 100 10h = 100 Divide each side by '10'. h = 10 Simplifying h = 10
| 5(-1)-y=7 | | 6-(r+2)=5(3r-4) | | x(x-12)+5=-30 | | log1/2(1)=x | | X/8-9=-6 | | 3j+4-j=5j-10-j | | 3(x•2)=96/2 | | X+40+106=180 | | 1-3x+4=-1-2c | | 9d-8=83 | | 2-0.8(2k-7)=1.2(k+1) | | (4-5x)/2=7 | | 1200=40x+20(1.5x) | | -2x+12=8x-8x | | 3(y-9)=12 | | d=5x+5y | | 35+.5x=20-.9x | | 8y-7=10y+11 | | 3x-100=3x+70 | | -61-11x=17-8x | | (-4x/6)-(-x-3) | | (-3a^3b)(-2b^4)(-a^4b^3)=equation | | (X^2)-(10x)+17=-4 | | -4m-13=3m+3-5m | | 16x^2+368x-2035=0 | | 3-8[3-(2y-9)]= | | -3.8+(-5.6)= | | 9÷3/5 | | 3.2=9 | | 15600=(200-10x)(90+5x) | | 5(v-6)=-2v+2 | | 2x+2y+2z=110 |